Analisis Pemanfaatan pada Bidang Pelaksanaan Pembangunan dalam Mendukung SDGs Desa di Desa Bojongkulur - Muhammad Egi Pratama Haedy; Rida Prihatni; Etty Gurendrawati (International Forum of Researchers and Lecturers, 2026)
This study examines the utilisation of Village Funds in the Village Development Implementation Sector to support the achievement of the Village Sustainable Development Goals (Village SDGs) in Bojongkulur Village. The analysis focuses on the alignment between development planning, programme implementation, and the contribution of Village Fund utilisation to achieving the Village SDGs. A qualitative case study approach was employed. Data were generated through in-depth interviews and document analysis involving the Village Head, Head of Finance Affairs, Development Implementation Officer, and community representatives selected using purposive sampling based on their involvement in and understanding of Village Fund management. The collected data were analysed using the Miles and Huberman interactive analysis model. The findings indicate that Village Funds have been utilised in accordance with development planning documents and prevailing regulations, with infrastructure development remaining the primary priority. Although several adjustments were required due to policy changes and local conditions, most development activities were implemented as planned. The utilisation of Village Funds has contributed to improving infrastructure quality, expanding access to public services, and enhancing community welfare, thereby supporting the achievement of the Village SDGs. Nevertheless, Village Fund allocation continues to be concentrated on physical infrastructure, highlighting the need to strengthen social, economic, and environmental development to achieve more balanced and sustainable rural development.